Membangun Fondasi Numerasi Siswa Dengan Permainan Ular Tangga Dan Kuis Matematika SD Negeri 106 Pekanbaru - Riswanda, Lisa Nurfaiza; Zufriady; Witri, Gustimal; Fendrik, Muhammad (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
Numeracy is the ability to understand and use numbers and mathematical concepts in the context of everyday life, including explaining quantitative information and solving practical problems. To improve this ability, mathematical knowledge will be applied in real situations, one of which is by playing the Snakes and Ladders game and giving mathematics quizzes. This activity is expected to help practice numeracy skills such as recognizing numbers, counting backwards, and understanding the relationship between numbers. While playing, students can answer quizzes to continue the steps in the game. Children are stimulated to understand and apply mathematical concepts in relevant contexts and their self-confidence increases, especially in their mathematical abilities. The purpose of this article is as an effort to build and improve children's numeracy in understanding mathematical concepts from basics to formulas and solutions which will be played by all students from grades 1 to 6 at SD Negeri 106 Pekanbaru in groups. From the program that we implemented at SD 106 Pekanbaru, results were obtained in the form of mastery of mathematical questions starting from basic questions, concepts and formulas by all students.